Performance evaluation of wire electrical discharge machining on Titanium Alloy - Tan, Jun Qi; Mohd Yazid, Abu (Universiti Malaysia Pahang, 2018)
The experimental carried out to aim at the selection of the best condition machining parameter combination for wire electrical discharge machining (WEDM) of titanium alloy (Ti–6Al–4V). By using Design Expert 10 software, a series of experiments were performed by selecting pulse-on time, pulse-off time, servo voltage and peak current as parameters. The responses that considered were cutting speed, material removal rate, sparking gap and surface roughness. Based on ANOVA analysis, the effect from the parameters on the responses was determined. The optimum machining parameters setting for the maximum cutting speed, minimum sparking gap and minimum surface roughness were found by proceed optimization experiment. Then, each optimization response had their own combination setting on WEDM to cut titanium alloy. 3D response surface graph such as dome and bowl shape represent maximum and minimum point for the solutions had shown in the report. Finally, predicted and actual value from the experiment have been calculated for validation.